1978
DOI: 10.1111/j.1365-2362.1978.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Human colonic adenylate cyclase: effects of bile acids

Abstract: Three different bile acids--deoxycholic acid, chenodeoxycholic acid and ursodeoxycholic acid--were tested for their capacity to stimulate the adenylate cyclase in human colonic mucosa. This enzyme system was found to be sensitive towards vasoactive intestinal polypeptide and prostaglandin E2. These three bile acids were ineffective in activating the human cyclase system over a wide concentration range tested. Concentrations above 1 X 10(-5) mmol/l induced a dose-dependent inhibition of basal enzyme activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In contrast, both agents caused at higher concentration inhibition of the enzyme. Furthermore, Simon et al (1978) and Simon & Kather (1980) showed that deoxycholic acid and other unconjugated bile acids plus ricinoleic acid and dioctylsulphosuccinate all acted inhibitory on preparations both of AC and phosphodiesterase (=PDE) obtained from human colonic biopsies. Since dioctylsulphosuccinate in contrast to the other agents caused inhibition of PDE at lower concentrations than those required to inhibit AC, Simon & Kather (1980) suggested that the drug might induce cAMP accumulation by PDE inhibi-tion rather than by AC stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, both agents caused at higher concentration inhibition of the enzyme. Furthermore, Simon et al (1978) and Simon & Kather (1980) showed that deoxycholic acid and other unconjugated bile acids plus ricinoleic acid and dioctylsulphosuccinate all acted inhibitory on preparations both of AC and phosphodiesterase (=PDE) obtained from human colonic biopsies. Since dioctylsulphosuccinate in contrast to the other agents caused inhibition of PDE at lower concentrations than those required to inhibit AC, Simon & Kather (1980) suggested that the drug might induce cAMP accumulation by PDE inhibi-tion rather than by AC stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The question has been raised if also hydragogue drugs may act o n this system, and research along this line has been stimulated Briseid et al 1976Briseid et al & 1977Conley et al 1976a & b;Coyne et al 1976Coyne et al & 1977Donowitz & Binder 1975;Gaginella et ai. 1978;Loeschke 1979;Simon et al 1978;S i m o n & Kather 1980;S u n d & Hillestad 1978), with different results a s t o the significance of t h e system f o r t h e hydragogue effects. Consequently, we decided t o study the interaction of synthetic surfactants ( a n d of deoxycholic acid) with the adenylate cyclase/ c A M P system u n d e r experimental conditions where our former studies (Sund 1978a;S u n d & Matheson 1978) demonstrated a significant alteration of mucosal transport.…”
mentioning
confidence: 99%
“…For example , recent studies by Simon et at. were unable to show that bile acid-induced diarrhea was associated with activation of memo brane-bound adenylate cyclase in man (40).…”
mentioning
confidence: 91%